2017
DOI: 10.1016/j.gde.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic mechanisms for axon regeneration: insights from injured axons in Drosophila

Abstract: Axonal damage and loss are common and negative consequences of neuronal injuries, and also occur in some neurodegenerative diseases. For neurons to have a chance to repair their connections, they need to survive the damage, initiate new axonal growth, and ultimately establish new synaptic connections. This review discusses how recent work in Drosophila models have informed our understanding of the cellular pathways used by neurons to respond to axonal injuries. Similarly to mammalian neurons, Drosophila neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 56 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…The nematode Caenorhabditis elegans provides several unique advantages, including optical transparency, the possibility of genetic manipulation and the availability of methods to axotomize single axons with a laser 14 . A number of different injury paradigms have also been used in the larval and adult nervous system of the fruitfly Drosophila melanogaster , which also enables the power of live imaging to be combined with genetic manipulation 16 . Other animals used to study injury responses include Aplysia, which has been instrumental in demonstrating the existence of positive injury signals 217 , lamprey, which possess both regenerating and non-regenerating CNS neurons 17 , and the axolotl, which can also regenerate its spinal cord following complete transection 218 .…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The nematode Caenorhabditis elegans provides several unique advantages, including optical transparency, the possibility of genetic manipulation and the availability of methods to axotomize single axons with a laser 14 . A number of different injury paradigms have also been used in the larval and adult nervous system of the fruitfly Drosophila melanogaster , which also enables the power of live imaging to be combined with genetic manipulation 16 . Other animals used to study injury responses include Aplysia, which has been instrumental in demonstrating the existence of positive injury signals 217 , lamprey, which possess both regenerating and non-regenerating CNS neurons 17 , and the axolotl, which can also regenerate its spinal cord following complete transection 218 .…”
Section: Figmentioning
confidence: 99%
“…Other aspects of axon regeneration, which include the roles of the cellular environment, axon–soma signalling and growth cone formation and dynamics have been extensively covered in recent reviews 4,5,8,1013 and will not be discussed here. This Review largely focuses on studies on mice, as recent reviews have covered axon regeneration in other model systems including C. elegans 14,15 , Drosophila melanogaster 16 and fish 17 .…”
mentioning
confidence: 99%
“…Importantly, DLK’s actions and signaling mechanisms appear specifically tuned to axonal damage and not dendrite damage: in contrast to axonal regeneration, DLK is not required for the regrowth of dendrites following injury [35,36•]. In addition, certain cell body responses to axonal injury induced by DLK are not induced by dendritic injury [3739]. …”
Section: Dlk Regulates Retrograde Responses To Axonal Damage and Tropmentioning
confidence: 99%
“…In this study we found that synaptic defects in embryonic unc-104-null mutants, including the failure to form synaptic boutons and AZs, arise not from direct loss of Unc-104 transport function, but via an indirect mechanism, which involves activation of the Wnd/DLK axonal damage signaling pathway. The Wnd/DLK mixed lineage kinase has recently received intense interest for its roles in regulating both regenerative and degenerative responses to axonal damage in vertebrate and invertebrate neurons ( Gerdts et al, 2016 ; Hao and Collins, 2017 ; Li and Collins, 2017 ; Tedeschi and Bradke, 2013 ). We found that the Wnd/DLK signaling pathway becomes activated when Unc-104’s function is impaired, and then promotes synaptic dysfunction by restraining expression of multiple pre-synaptic AZ and SV protein components.…”
Section: Introductionmentioning
confidence: 99%